The Differences of Asian and Western Consumers' Attitudes towards Brand Extensions by Information Types: Attribute-Related vs. Non-Attribute-Related Information - Jae Jin Lee; Sung-Jun Lee (International Review of Management and Marketing, 2017)
This study aims to empirically examine how Asian and Western consumers with different cultural backgrounds (holistic vs. analytic thinking) in different brand extension situations (high vs. low brand-extension fit) perceive two different types of brand extension information (attribute-related vs. non-attribute-related information). The previous brand extension studies have demonstrated that Asian consumers are considerably better in recognizing fit between parent brands and their extensions than Western consumers. However, only few studies have been conducted so far to investigate how firms can effectively communicate with consumers from different cultures when extending their existing brands. For that, an inter-subjects experiment consisting of 2 (high vs. low similarity with parent brands) * 2 (attribute-related vs. non-attribute-related information) * 2 (Asian vs. Western consumers) groups was conducted with the samples from South Korea, US, Canada and France (N=393). As a result, Westerners tended to show more favour to attribute-related information than Asians when brand-extension fit was high. When brand-extension fit was low, however, Asians tended to show more favour to attribute-related information than Westerners. In addition, Asians overall showed more favour to low-similarity extensions compared to Westerners when non-attitude-related information was suggested.